Landscape context and substrate characteristics shape fungal communities of dead spruce in urban and semi‐natural forests. (26th January 2022) - Korhonen, Aku; Miettinen, Otto; Kotze, Johan D.; Hamberg, Leena
Summary: Urban green areas are becoming increasingly recognized for their biodiversity potential. However, little is known about how urbanization shapes cryptic species communities, such as those residing in deadwood. In this study, we investigated downed Norway spruce trunks at intermediate stages of decay, in urban and semi‐natural forests in southern Finland. To understand the interconnections between landscape context, deadwood characteristics and wood‐inhabiting fungal communities, we studied structural characteristics, surface epiphyte cover and internal moisture and temperature conditions of the tree trunks, and fungal communities residing in the wood. Our findings showed that urban tree trunks had less epiphyte cover and lower moisture than trunks in semi‐natural forests. Overall, urban forests provide less favourable habitats for a majority of the dominant wood‐inhabiting fungal species and for red‐listed species as a group. Yet, 33% of urban trunks hosted at least one red‐listed species. While these landscape‐scale effects may be driven by local climatic conditions as well as contingencies related to available species pools, our results also highlight the significance of substrate‐scale variability of deadwood in shaping wood‐inhabiting fungal communities. We show that epiphyte cover is a significant driver or indicator of these small‐scale dynamic processes in deadwood.